Postoperative necrotizing fasciitis of the thorax in cardiac surgery - Frota Filho,José Dario (2001)
Necrotizing fasciitis is a rare soft tissue infection and a life-threatening emergency, often fatal. Its incidence and management are described plentifully in the medical literature regarding the most common anatomical sites involved like the abdomen, lower and upper limbs, and perineum. However, available data and case reports of chest wall necrotizing fasciitis after thoracic procedures are scarce, mainly after major cardiac operations. We report and discuss a case of necrotizing fasciitis of the chest wall occurring in the immediate postoperative period of a cardiac procedure, and include a brief review of the concepts, pathophysiology, and treatment reported in the medical literature. We emphasize the need for early diagnosis and urgent and effective surgical debridement. Of importance is the fact that we have not found any references in the literature to cases similar or equal to the one we describe here, which occurred in the postoperative period of a cardiac procedure.